(untitled) (Research, Society and Development, 2021)
The present study approaches the theme of the Scheme Therapy (ST) in the treatment of cluster B personality disorders, having as objective to verify the effectiveness of the Scheme Therapy (ST) in the treatment of Cluster B personality disorders, identifying in the scientific literature on the subject the main techniques used in the Scheme Therapy for the treatment of the Narcissistic, Antisocial, Borderline, and Histrionic personality disorders. The type of research conducted was a qualitative literature review. Data collection was carried out from March to May 2021. The bibliographic material used was national and international books and articles found in the databases Bireme (Virtual Health Library), Scielo, Pepsic, Web of Science, Pubmed, and Google Academic. The main results obtained were through studies based on scientific evidence that point out that the ST presents important results for the disorders addressed, just like the techniques used by this line, it is also emphasized that the ST provides greater functionality and quality of life to the subject. Based on the studies analyzed, we conclude that the treatment in the clinical context of patients with Cluster B personality disorders can present significant evolution in the cognitive, emotional and relational aspects of their lives, pointing to positive indications of the effectiveness of Scheme Therapy in refractory cases.